2016
DOI: 10.1155/2016/1678495
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Intraocular Methotrexate in the Treatment of Posterior Uveitis in Behçet’s Disease Patients Compared to Retrobulbar Steroids Injection

Abstract: Aim of Work. To evaluate the efficacy of intravitreal methotrexate (MTX) compared to retrobulbar triamcinolone acetonide (TAA), in controlling posterior segment involvement and inducing remissions among Behçet's disease (BD) patients. Study Design. This is a cross-sectional nonrandomized comparative study. Patients and Methods. 31 adult BD male patients with a mean disease duration of 5.45 years who presented with bilateral posterior segment involvement were included. Each patient received intravitreal injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…MTX is water-soluble and it has been intravitreally administered as an off-tag treatment for inflammatory ocular diseases such as retina uveitis. [64][65][66] Thus, the novel activity of MTX in the selective clearance of the P23H rhodopsin and its retinal protective effects in the Rho P23H/+ mice make this drug with a therapeutic potential to be repurposed for the treatment of RHO-associated adRP.…”
Section: Discussionmentioning
confidence: 99%
“…MTX is water-soluble and it has been intravitreally administered as an off-tag treatment for inflammatory ocular diseases such as retina uveitis. [64][65][66] Thus, the novel activity of MTX in the selective clearance of the P23H rhodopsin and its retinal protective effects in the Rho P23H/+ mice make this drug with a therapeutic potential to be repurposed for the treatment of RHO-associated adRP.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, Khalil et al found no significant changes in the mean IOP values with intravitreal MTX. 20 Some studies have recently demonstrated that using intravitreal anti-VEGF injection decreases NO and PGI2 production and induces vasoconstriction and a tendency for hypertension. Intravitreal anti-VEGF can also promote thrombosis formation and the tendency for cardiovascular and cerebral events.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, it also reduced the need for systemic immunosuppressive drugs. In another study, Khalil and coworkers, [57] evaluated the efficacy of intravitreal MTX in controlling posterior segment involvement of Behcet's disease (BD) in comparison to retrobulbar triamcinolone acetonide (TA). They showed that improvement of anterior chamber reaction and vitreous inflammation was similar between the two groups; however, relapses were noted less in patients who received intravitreal injection of 400 µg MTX.…”
Section: Intraocular Tumors (I) Retinoblastomamentioning
confidence: 99%